State Park Xixová-Japuí: analysis of the relationship with the entorno population (Quarter Japuí) - Correa Lau, Michele; Moledo de Souza Abessa, Denis; Hartung Toppa, Rogério (O Mundo da Saúde, 2011)
This work analyzes the interactions between the community of Japuí Quarter, in the city of São Vicente (SP), and Xixová-Japuí (PEXJ) State Park. For doing this, a semi-structured questionnaire was applied to inhabitants of the quarter and actors related to the Park, including its manager at the time, approaching aspects on environmental information, interaction with the UC (Unit of Conservation) territory, knowledge and availability of information on the Park. The results showed a low middle class population with low degree of instruction in general. The relationship of the community with PEXJ management was almost nonexistent, something which may result from the fact the population are not considered by the UC. One also proved the low knowledge and interest on the Park by inhabitants, as well as the failure of the administration, until that moment, in inserting the community in the unit’s discussion and management. Such situation allowed the establishment of a conflicting relationship between the PEXJ and members of the community, leading to a situation where management has not established participative actions.